2016
DOI: 10.1371/journal.pone.0153854
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Crop Damage by Protected Wild Mammalian Herbivores on the Western Boundary of Tadoba-Andhari Tiger Reserve (TATR), Central India

Abstract: Crop raiding by wild herbivores close to an area of protected wildlife is a serious problem that can potentially undermine conservation efforts. Since there is orders of magnitude difference between farmers’ perception of damage and the compensation given by the government, an objective and realistic estimate of damage was found essential. We employed four different approaches to estimate the extent of and patterns in crop damage by wild herbivores along the western boundary of Tadoba-Andhari Tiger Reserve in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 29 publications
2
41
0
1
Order By: Relevance
“…Animal husbandry and agriculture are important part of household's livelihoods and incomes in human dominated mid-hills that creates competition between local communities and wildlife for the use of natural resources, that creates escalating conflict (Bayani et al 2016). Total loss of livestock predation per household in ACA at US $ 95 in 2009 and US$ 42 in 2010, with leopards blamed for 94.9 % of the losses (Koirala et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Animal husbandry and agriculture are important part of household's livelihoods and incomes in human dominated mid-hills that creates competition between local communities and wildlife for the use of natural resources, that creates escalating conflict (Bayani et al 2016). Total loss of livestock predation per household in ACA at US $ 95 in 2009 and US$ 42 in 2010, with leopards blamed for 94.9 % of the losses (Koirala et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the damaged parts may regenerate but there is nevertheless a substantial amount of loss in terms of total yield (Bayani et al 2016). In contrast, for some crops such as chickpea, herbivory in first 20 days after sowing may actually lead to greater branching resulting in more number of seeds.…”
mentioning
confidence: 99%
“…In contrast, for some crops such as chickpea, herbivory in first 20 days after sowing may actually lead to greater branching resulting in more number of seeds. However, herbivory beyond a threshold in pre-flowering stage is known to decrease crop yield even in chickpea by as much as 67% (Bayani et al 2016).…”
mentioning
confidence: 99%
“…Most of these families are Scheduled Tribe (48%) or Scheduled Caste (11%) 11 , with 41% recorded as other caste. Villagers located in the buffer zone of TATR have, historically, relied predominantly on agriculture for livelihoods (Bayani et al, 2016). Village members typically intercrop rice and soybean in the monsoon season (referred to as kharif crops), with wheat and chickpea in the winter season (rabi crops).…”
Section: Study Area: Tadoba-andhari Tiger Reservementioning
confidence: 99%
“…Whilst government authorities are expected to compensate farmers for the loss of crop damage from wildlife in these buffer zones, a recent study found that the assessment method typically employed grossly underestimates actual damage. Hence, compensation often falls well short of the actual loss incurred (Bayani et al, 2016), a trend that has been found to be consistent across India (Ogra andBadola, 2008, Mishra, 2002), and elsewhere (Barua et al, 2013). Recognizing the reinforcing role of agricultural practices and increased risk of human-wildlife conflict, in addition to known pitfalls and limitations of compensation schemes (African Elephant Specialty Group of IUCN, 2000), the 13 "RI" corresponds to the research informant, whilst "FP" in subsequent quotes corresponds to focus group participant.…”
Section: Human-wildlife Conflict At Tatrmentioning
confidence: 99%